Underwater delay-tolerant routing via probabilistic spraying - Azad, Saiful; Casari, Paolo; Zanforlin, Marco; Zorzi, Michèle (IEEE, 2018)
We propose underwater delay-tolerant routing via probabilistic spraying (UDTN-Prob), a routing protocol for underwater delay-tolerant networks based on the store-and-forward paradigm. Our protocol exploits limited statistical knowledge of the time between two subsequent contacts between pairs of network nodes in order to filter the packets injected into the network, so that only those with a sufficiently high chance of being delivered to their intended destination within a given deadline are actually transmitted. In addition, the foreseen duration of a contact is estimated via a preliminary packet exchange, so that the nodes get a fair share of the contact time to exchange their own data. The transmission is protected against channel-induced packet losses via an automatic repeat query scheme modified to adapt itself to typical underwater transmission times and to the variation of round-trip times induced by node mobility. We simulate the protocol using the DESERT Underwater libraries, that make it possible to accurately reproduce the nodes’ behavior and mobility patterns. Our results show that the proposed protocol achieves significantly better performance than spray-and-wait, which is currently the most typical choice among store-and-forward protocols. Moreover, we show that a two-hop statistical knowledge of the node contact process yields marginally higher utility with respect to a simpler one-hop knowledge, which is also much easier to collect or estimate.